Quality Characteristic of Tempeh Nuggets with Fortification of Chicken Egg Shell Powder - Usman Pato; Asti Dian Ramadhani Prihartini; Emma Riftyan (Agriculture Faculty, 2025)
Some previous studies have utilized egg shell powder as a fortification of food products made which aims to see the effect of egg shell powder addition on the calcium content and quality of the product. Nuggets is a product that really consume by society at this time, but widely circulated nuggets in the market are generally high in fat and low calcium. Chicken egg shell powder contains a farly high calcium. The purpose of this research is to obtain the best concentration of chicken egg shell powder on calcium content and quality of tempeh nugget. The treatment in this research was addition of egg shell powder in different concentrations, namely TC0 without egg shell powder, TC1 5% addition of shell powder, TC2 10% addition of shell powder, TC3 15% addition of shell powder. The data obtained were analyzed statistically using the ANOVA test. If the calculated F value is greater than or equal to the F table, then continue with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that the addition of egg shell powder significantly affected moisture, ash, protein, fat, and calcium content. The optimal concentration of chicken egg shell powder on calcium content and quality of tempeh nugget was TC1 with moisture content of 49.69%, ash of 4.81%, protein of 13.54%, fat of 2.38%, calcium of 421.87 mg/100 g nugget. The descriptive sensory test results had a yellow color, smelled of tempeh, tasted of tempeh, and had a bit sandy texture